HOW CAN COLLEGES ADDRESS THE ISSUE OF FOOD INSECURITY AMONG STUDENTS? - Rukhshona Tajiboyeva; Fozilbek Orzibekov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The issue of college students' food security has grown significantly, and more and more students are finding it difficult to get enough wholesome food. Students' general well-being, mental health, and academic achievement are all significantly impacted by this issue. This study intends to investigate the prevalence and consequences of food insecurity among college students, considering the contributing variables, and offering suggestions for resolving this issue. The study used a combination of approaches, such as surveys and interviews, to determine that the main variables influencing food security were lack of access to reasonably priced food and financial challenges. The results highlight the negative impact on academic performance and mental health, and also emphasize the importance of reducing stigma and expanding support programs. In order to effectively address food security, the essay ends with suggestions for colleges to more broadly adopt financial literacy initiatives, community partnerships, and food aid techniques.